Energy and environmental study of the replacement of a cellulose pulp mill as an environmental gain - Francisco Savastano Neto (Revista Ambiente & Água, 2013)
A significant fraction of the energy spent in Brazil is associated with industrial consumption (40.6%). The purpose of this work was to demonstrate one of many ways to reduce electric energy consumption by the industry and, consequently, reduce emissions associated with the generation, transmission, and consumption of this resource. The search for energetic efficiency, coupled with economic, social, and environmental practices can shift the industry in the direction of sustainability. The emission of CO2/kWh was chosen as a sustainability indicator to monitor the energy consumption pattern during the development of this research. The main objective was to assess the reduction of greenhouse gas emissions associated with a more efficient electric energy consumption strategy adopted by a large manufacturer. At this company, a cellulose pulp milling system used during a diaper manufacturing process was replaced by another system with higher efficiency. Energy consumption was reduced by 60%, and greenhouse gas emissions were reduced by an estimated 80 ton/year of carbon dioxide (CO2). These results demonstrate the relationship between adopting a more energy efficient system and a reduction in greenhouse gas emissions. Moreover, these practices contribute to significant industrial cost reduction.